2008
DOI: 10.1016/j.jml.2007.06.010
|View full text |Cite
|
Sign up to set email alerts
|

A content-addressable pointer mechanism underlies comprehension of verb-phrase ellipsis☆

Abstract: Interpreting a verb-phrase ellipsis (VP ellipsis) requires accessing an antecedent in memory, and then integrating a representation of this antecedent into the local context. We investigated the online interpretation of VP ellipsis in an eye-tracking experiment and four speed-accuracy tradeoff experiments. To investigate whether the antecedent for a VP ellipsis is accessed with a search or direct-access retrieval process, Experiments 1 and 2 measured the effect of the distance between an ellipsis and its antec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
185
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(202 citation statements)
references
References 70 publications
16
185
1
Order By: Relevance
“…Importantly, its antecedents bear no special marking that might engage special memory strategies upon encountering the antecedent. Behavioral studies of ellipsis processing have shown that interpreting more material within the dependency decreased the likelihood of successful retrieval and interpretation (Martin and McElree, 2008, consistent with a cue-based interference account.…”
Section: Cue-based Retrieval Interference During Processing Of Ellipsismentioning
confidence: 54%
See 1 more Smart Citation
“…Importantly, its antecedents bear no special marking that might engage special memory strategies upon encountering the antecedent. Behavioral studies of ellipsis processing have shown that interpreting more material within the dependency decreased the likelihood of successful retrieval and interpretation (Martin and McElree, 2008, consistent with a cue-based interference account.…”
Section: Cue-based Retrieval Interference During Processing Of Ellipsismentioning
confidence: 54%
“…Within hierarchical models such as the neurocognitive model of auditory sentence comprehension (Friederici, 2002), retrieval cues could shape many aspects of processing (from as early as word identification to later stages like structure building and construction of semantic relations), if they are conceived of as multiplicative composites of information maintained in the current focus of attention that retrieve or point to representations as processing requires (Gillund and Shiffrin, 1984;Lewis et al, 2006;Martin and McElree, 2008;McElree, 2006). In this way, as general "working memory" appears alongside the online language processing stream in the model, cues could also serve as interfaces between nodes in the different processing streams, perhaps with degree of cue-diagnosticity capturing some of the two-stage processing bottlenecks that have been classically observed in the literature.…”
Section: Potential Implications For Neurocognitive Accounts Of Sentenmentioning
confidence: 99%
“…While it is not itself an antecedent search mechanism, the structural identity constraint may interact with the process of locating candidate antecedents in particular ways. If an antecedent search mechanism (such as the content-addressable pointer mechanism proposed by Martin and McElree (2008), or the mechanism proposed by Arregui et al (2006), which looks for candidate antecedents in canonical VP positions) identifies a number of candidate antecedents, the structural constraint may bias the comprehender toward one potential antecedent over another, based on the degree to which structural identity is satisfied or violated.…”
Section: Discussionmentioning
confidence: 99%
“…'While', is one instance of a subordinating conjunction, and if these subtle differences in syntactic constraint impact parallelism effects we should see a reduced modulation of parallelism effects for 'while' than 'but'. Alternatively, the meaning of the conjunction may be what modulates constituent order parallelism 3 For a discussion of alternatives such as copy-a (Frazier & Clifton, 2001) or pointers to representations in memory (Martin & McElree, 2008) see Knoeferle and Crocker (2009). 4 See Callahan, Shapiro, and Love (2010) for evidence on the re-activation of verb meaning in response to a related vs. unrelated probe word following the conjunction and, and see Poirier, Walenski, and Shapiro (2011) for relevant evidence on anaphora processing.…”
Section: The Compositional Semantic Interpretation Accountmentioning
confidence: 99%